Uporządkuj jednomiany
a) y*6x =
b) -5b*7ba*(-2) =
c) x*(-6)x*y =
d) 2x*3x(do kwadratu ) =
e) 12cd*0,2c(do kwadratu) * d( do sześcianu )
f) (-x)*(-a)*12a*(0,3x(do kwadratu ) =

Przedstaw w jak najprostszej postaci
a) 16x-5y-6-21x+19y-8 =
b) -(9a-b+7) + ( 6+a-8b ) =
c) 5(x-3y) - 4(x-2)+(y-1) =
d) 2x(4,1 xy - 0,5y +3,2x) - (5x(do kwadratu) - 3,4xy + 1,2x (do kwadratu) y) * 3
e) (3x-5) - (2x + 4)=
f) 4(3x - 5) - 3(2x+4)=
g) (7x-3) -4 (2x+4)+7x
h) 5(a-b)-7a (a-b)

1

Odpowiedzi

2010-03-25T20:10:59+01:00
Wydaje mi się że
Uporządkuj jednomiany:
a) 6xy
b)70ab (do kwadratu)
c)-6x(do kwadratu)y
d)6x ( do sześcianu)
e) 2.4c ( do sześcianu)d ( do czwartej)

Przedstaw w jak najprostszej postaci:
b)-9a+b-7+6+a-8b= -1-9a ( do kwadratu)albo 10a(nie jestem pewna)-7b
c) 5x-15y - 4x+8+y-1 = x -14y +7
e) 3x-5 -2x-4=x- 9
f) 12x - 20 - 6x-12=6x- 32
h) 5a-5b)-7a(do kwadratu)+ 7ab